Implicit interest as price discrimination in the bank deposit market - Juha Tarkka (Bank of Finland, 1994)
1n this paper the theory af nonlinear multiproduct pricing is applied to the problem of determining the terms af liquid bank deposits such as cheque accounts. The prafit maximizing interest rate and service charge schedules are characterized within a madel of a manopolybank with a heterogeneous clientele. It is shown that the practice of "implicit interest", meaning below-cost pricing of payment services parallel with large interest margins on deposits, may well be part of the optimal price discrimination strategy. It is also shown that necessary conditians for that kind of cross subsidization to be optimal exist in an inventary theoretic madel of the demand for cheque account services. It is argued that the failure to take (second-degree) price discrimination into account invalidates much of the previous research on demand deposit pricing.
URN:NBN:fi:bof-201808031874
Keywords: 330